Two new species of scale worms (Polychaeta: Aphroditiformia) from deep-sea habitats in the Gulf of Cadiz (NE Atlantic) - Ravara, Ascensão; Cunha, Marina R. (Zootaxa, 2016)
Two new species of scale worms are described from the Gulf of Cadiz (NE Atlantic), at depths between 1100 and 2230 m. Australaugeneria iberica sp. nov. (Polynoidae) was obtained from an alcyonarian colony collected at the flank of Carlos Ribeiro mud volcano; it is characterized by the presence of neuropodial hooks only on segment two and by having the first parapodia not enlarged. This is the first report of the genus for the deep sea. The diagnosis of Australaugeneria is emended and a table comparing all species of the genus is provided. Pholoe petersenae sp. nov. (Pholoidae) was collected from the crater of three mud volcanoes (Darwin, Captain Arutyunov and Carlos Ribeiro) in areas of active seepage. This species is characterized by the presence of prostomial peaks and parapodia stylodes and the absence of eyes.